Palladium-Catalyzed Domino Carbopalladation/C–H Activation for the Synthesis of Tetrasubstituted Alkenes Bearing Five- and Seven-Membered Rings - Tietze, Lutz F.; Hungerland, Tim; Depken, Christian; Maaß, Christian; Stalke, Dietmar (Synlett, 2012)
A Pd-catalyzed domino carbopalladation/C–H-activation reaction of phenoxyphenyl-substituted propargylic alcohols was used for the synthesis of tetrasubstituted alkenes bearing either a dihydroindene or benzo[7]annulene motif. These compounds are of interest for the construction of molecular switches and motors.
Keywords: palladium; domino reaction; C–H activation; tetrasubstituted alkenes; catalysis